Ladislaus II Jagiełło (1386–1434) - Mateusz Grzęda (Encyclopedia, 2022)
Ladislaus II Jagiełło (1386–1434). Ladislaus II Jagiełło is the founder of the Jagiellonian dynasty that had ruled over Poland and the Grand Duchy of Lithuania (until 1572), Bohemia (1471–1526) and Hungary (1440–1444, 1490–1526). A Grand Duke of Lithuania from 1377, and from 1386 a king of Poland and lord of Lithuania, which he ruled jointly with his cousin Witold (Vytautas), the son of Kęstutis. Five medieval portraits of Jagiełło survive, four of which date from the period of his reign in the Polish–Lithuanian state and one was executed posthumously. The earliest image, on Jagiełło’s Great Seal, was made in connection with his coronation as king of Poland (1386). Two portraits in the Holy Trinity Chapel at the Castle of Lublin (1418) are part of a wall paintings scheme commissioned by the monarch and executed by a team of painters brought from Ruthenia. Furthermore, the sumptuous tomb (before 1430) in Cracow was commissioned by the king. Its top slab bears an effigy of Jagiełło with his suggestively rendered countenance, which undoubtedly reflects the actual facial features of the elderly monarch. An image of the king represented as one of the Three Magi in a panel of an altarpiece in the tomb chapel of Casimir IV Jagiellonian, Jagiełło’s son and his successor on the Polish throne, dates from 1470. The chapel dedicated to the Holy Cross, erected at Cracow Cathedral, was in all likelihood commissioned by Casimir himself and his consort Elizabeth of Austria.